Perjumpaan dan Relasi Damai Islam-Kristen - Christ; Parhusip, Bintang; Manik, Iman Jaya; Doa, Alfonsa Tawa; Situmorang, Kalaudius Willy (Aditya Wacana Pusat Pengkajian Agama Dan Kebudayaan, 2021)
This study pays attention to the stories or discussions that shape the peaceful encounters and relations between Islam and Christianity. Historically these two Abrahamic religions have been in conflict and neglected peace building. The methodology used in this research is interviews with several academics. The results are translated into published sources or important documents from both sides (Islam and Christianity). Based on the recommendations and analyzes of academics and from existing documents, it was found that the leaders of the two religions had tried to live in peace with concrete actions. Through their respective leaders today, these two major religions want a relationship and cooperation based on the law of love. Relationships can be built by knowing each other’s teachings properly and being open to accepting each other’s differences. To live together in diversity in this country (Indonesia), the authors feel the urgency to carry out a constructive inclusive dialogue.